High Growth Rate of Diatoms Explained by Reduced Carbon Requirement and Low Energy Cost of Silica Deposition - Keisuke Inomura; Juan José Pierella Karlusich; Stephanie Dutkiewicz; Curtis Deutsch; Paul J. Harrison; Chris Bowler (Microbiology Spectrum, 2023)
ABSTRACT The rapid growth of diatoms makes them one of the most pervasive and productive types of plankton in the world’s ocean, but the physiological basis for their high growth rates remains poorly understood. Here, we evaluate the factors that elevate diatom growth rates, relative to other plankton, using a steady-state metabolic flux model that computes the photosynthetic C source from intracellular light attenuation and the carbon cost of growth from empirical cell C quotas, across a wide range of cell sizes. For both diatoms and other phytoplankton, growth rates decline with increased cell volume, consistent with observations, because the C cost of division increases with size faster than photosynthesis. However, the model predicts overall higher growth rates for diatoms due to reduced C requirements and the low energetic cost of Si deposition. The C savings from the silica frustule are supported by metatranscriptomic data from Tara Oceans, which show that the abundance of transcripts for cytoskeleton components in diatoms is lower than in other phytoplankton. Our results highlight the importance of understanding the origins of phylogenetic differences in cellular C quotas, and suggest that the evolution of silica frustules may play a critical role in the global dominance of marine diatoms. IMPORTANCE This study addresses a longstanding issue regarding diatoms, namely, their fast growth. Diatoms, which broadly are phytoplankton with silica frustules, are the world’s most productive microorganisms and dominate in polar and upwelling regions. Their dominance is largely supported by their high growth rate, but the physiological reasoning behind that characteristic has been obscure. In this study, we combine a quantitative model and metatranscriptomic approaches and show that diatoms' low carbon requirements and low energy costs for silica frustule production are the key factors supporting their fast growth. Our study suggests that the effective use of energy-efficient silica as a cellular structure, instead of carbon, enables diatoms to be the most productive organisms in the global ocean.